2020
DOI: 10.1021/acs.biomac.0c00358
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Core–Shell Glyconanoparticles for Galectin-3-Targeted, Trigger-Responsive Combination Chemotherapy

Abstract: Galectin-3 (gal-3) plays a crucial role in various cellular events associated to tumor metastasis and progression. In this direction, gal-3 binding core–shell glyconanoparticles based on citrus pectin (CP) have been designed for targeted, trigger-responsive combination drug delivery. Depolymerization via periodate oxidation in heterogeneous medium yielded low-molecular weight dialdehyde oligomers (CPDA) of CP with a gal-3 binding property (K d = 160.90 μM). CPDA-based core–shell nanoparticles prepared to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…For example, increased Gal-3 levels are often detected in cancer patients’ blood, indicating that circulating Gal contributes to microenvironment reprogramming during cancer progression [ 75 , 138 ]. Circulating Gal-3 interacts with endothelial cells, which induce cytokine production that promotes cancer progression [ 139 , 140 ]. Colomb et al showed that Gal-3 interacts with CD146 on endothelial cells through affinity purification assays, which leads to AKT signaling activation and IL-6 and G-CSF secretion to promote cancer progression [ 141 ].…”
Section: Galectin In the Microenvironmentmentioning
confidence: 99%
“…For example, increased Gal-3 levels are often detected in cancer patients’ blood, indicating that circulating Gal contributes to microenvironment reprogramming during cancer progression [ 75 , 138 ]. Circulating Gal-3 interacts with endothelial cells, which induce cytokine production that promotes cancer progression [ 139 , 140 ]. Colomb et al showed that Gal-3 interacts with CD146 on endothelial cells through affinity purification assays, which leads to AKT signaling activation and IL-6 and G-CSF secretion to promote cancer progression [ 141 ].…”
Section: Galectin In the Microenvironmentmentioning
confidence: 99%
“…Recently, Gal-3 binding core-shell glyconanoparticles based on citrus pectin, with Gal-3 inhibition properties, have been designed for targeted and combination drug delivery (Balakrishnan et al, 2020). These nanoparticles in vivo preferentialy accumulate in the Gal-3-expressing tissues of the gastrointestinal tract of mice suggesting their potential for targetspecific release of drug used in combination with glyconanoparticles based on citrus pectin and for specific Gal-3 targeting and inhibition of Gal-3-mediated processes (Balakrishnan et al, 2020).…”
Section: Therapeutic Effects Of Gal-3 Inhibitionmentioning
confidence: 99%
“…For that purpose, pH-responsive polymeric systems are particularly appealing to selectively release therapeutics by exploiting the various pH gradients that exist in specific cellular compartments. The application of these polymers can further be expanded to other biological applications, including tumor-targeted delivery of drugs, intracellular delivery of nucleic acids or proteins, treatment of inflammatory diseases, and oral administration. , For example, imines, hydrazides, hydrazones, orthoesters, and acetal linkages degrade selectively in response to pH changes. , Among them, the imine linkage is of particular interest owing to its sensitivity under different acidic conditions, facilitating its widespread utility as a stimuli-responsive linkage. , As a notable example, Xu and co-workers conjugated doxorubicin to polymers through imine bond and demonstrated its pH-controlled drug release in acidic environments . In addition, Banerjee and co-workers developed pH-responsive glyconanoparticles conjugated to drugs through imine linkages …”
Section: Introductionmentioning
confidence: 99%
“…17 developed pH-responsive glyconanoparticles conjugated to drugs through imine linkages. 18 Despite active investigations into the prodrug approach with various carriers and therapeutic agents, the difference in solubility between each component can raise significant issues for effective conjugation. 19,20 On the other hand, mechanochemistry offers an alternative means to overcome this solubility limitation by alleviating the need for solvents.…”
Section: ■ Introductionmentioning
confidence: 99%